The art of sight-reading: Influence of practice, playing tempo, complexity and cognitive skills on the eye–hand span in pianists. (July 2016) - Rosemann, Stephanie; Altenmüller, Eckart; Fahle, Manfred
Sight-reading is a skill required by musicians when they perform sheet music unknown to them. It demands sequential anticipatory eye fixation of notes immediately followed by motor execution. The distance between eye (fixation of a note) and hand position (tapping the corresponding key) is called eye-hand span (EHS). The aim of our study was to investigate the influence of practice, playing tempo and complexity of the music on the size of the EHS, as well as its relation to performance and cognitive skills (shape recognition, working memory, and mental speed). We used a sight-reading paradigm where nine pianists accompanied a pre-recorded flute voice, which also served as a time-keeper. After a practice phase, a second measurement of the EHS with same tempo and a third and fourth measurement with a different playing tempo followed. We found that the practice phase only slightly affected the EHS but that the EHS significantly changed according to playing tempo and complexity of the music. Furthermore the EHS correlated with quality of performance after practice and mental speed skills. Hence we conclude that the EHS seems to be characteristic for each musician, is developed over years of practice and is relatively independent of a short practice phase.